2008
DOI: 10.1080/14622200802412911
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity during anticipation of smoking-related and emotionally positive pictures in smokers and nonsmokers: A new measure of cue reactivity

Abstract: Previous studies have shown that a brain wave pattern known as stimulus preceding negativity (SPN) can index the anticipation of motivationally relevant events. The present study was the first to use SPN as an index of the motivational significance of smoking-related pictures. Emotionally positive and neutral pictures served as controls. The paradigm involved the following sequence: (a) presentation of a picture (S1) for 500 ms, (b) a fixation cross for 3,500 ms, (c) a second presentation (S2) of the same pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…computer, home environment) stimuli with the reinforcing effects of cybersex resulting in cue-reactivity and craving reactions, associated to repeated cybersex use elicited by conditioned stimuli. This is in line with literature on other behavioral and substance addictions (Braus et al, 2001;Garavan, Pankiewicz & Bloom, 2000;Goudriaan, De Ruiter, Van den Brink, Oosterlaan & Veltman, 2010;Gray, LaRowe & Upadhyaya, 2008;Grüsser et al, 2004;Ko et al, 2009;Parker & Gilbert, 2008;Starcke, Schlereth, Domaß, Schöler & Brand, 2012;Thalemann, Wölfling & Grüsser, 2007;Yang et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…computer, home environment) stimuli with the reinforcing effects of cybersex resulting in cue-reactivity and craving reactions, associated to repeated cybersex use elicited by conditioned stimuli. This is in line with literature on other behavioral and substance addictions (Braus et al, 2001;Garavan, Pankiewicz & Bloom, 2000;Goudriaan, De Ruiter, Van den Brink, Oosterlaan & Veltman, 2010;Gray, LaRowe & Upadhyaya, 2008;Grüsser et al, 2004;Ko et al, 2009;Parker & Gilbert, 2008;Starcke, Schlereth, Domaß, Schöler & Brand, 2012;Thalemann, Wölfling & Grüsser, 2007;Yang et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…Given the prevalence of environmental smoking-related cues, it is important to better understand smokers’ reactivity to these cues in order to prevent relapse more effectively. Consistent with this reported association between relapse and the presence of smoking cues, many laboratory studies have demonstrated that smokers have greater reactivity to cigarette-related cues than non-cigarette-related cues by measuring self-reported craving (Payne, Smith, Sturges, & Holleran, 1996; Sayette, Martin, Wertz, Shiffman, & Perrott, 2001; Tidey, Rohsenow, Kaplan, & Swift, 2005), attentional bias (Ehrman, et al, 2002; Hogarth, Mogg, Bradley, Duka, & Dickinson, 2003; Waters, Shiffman, Bradley, & Mogg, 2003), event-related potentials (Parker & Gilbert, 2008; Versace, Minnix, et al, 2011; Versace, et al, 2010) and hemodynamic response (David, et al, 2005; Due, Huettel, Hall, & Rubin, 2002; Smolka, et al, 2006). …”
Section: Introductionmentioning
confidence: 65%
“…First, as a clinical trial of smoking cessation, the study did not include nonsmokers and non-treatment-seeking smokers. Therefore, we were not able to evaluate the specificity of the cigarette-related cue reactivity, although nonsmokers have not been found to respond to smoking stimuli as smokers do (David, et al, 2005; Due, et al, 2002; Ehrman, et al, 2002; Hogarth, et al, 2003; Parker & Gilbert, 2008). We were also unable to evaluate whether intention to quit may modulate cigarette-related cue and affective reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking-related cues (e.g. the visual and olfactory stimuli associated with each puff) elicit subjective states that can trigger smoking and nicotine-seeking behaviour (Caggiula et al, 2001; Carter and Tiffany, 1999; Conklin et al, 2008; Cui et al, 2013; Garcia-Rodriguez et al, 2012; Gass et al, 2012; Miranda et al, 2008; Niaura et al, 1988; O′Brien et al, 1998; Parker and Gilbert, 2008; Rose, 2006; Tong et al, 2007; Winkler et al, 2011; Zhou et al, 2009). Accumulating data from animal studies have demonstrated a significant contribution of nicotine-associated cues to the resumption of nicotine-seeking behaviour (Abdolahi et al, 2010; Chiamulera et al, 2010; Cohen et al, 2005; Feltenstein et al, 2012; Fowler and Kenny, 2011; LeSage et al, 2004; Liu, 2010; Liu et al, 2006, 2008; Paterson et al, 2005; Shaham et al, 1997).…”
Section: Introductionmentioning
confidence: 99%